2022
DOI: 10.1007/s10534-022-00427-z
|View full text |Cite
|
Sign up to set email alerts
|

An overview on in vitro and in vivo antiviral activity of lactoferrin: its efficacy against SARS-CoV-2 infection

Abstract: Beyond the absolute and indisputable relevance and efficacy of anti-SARS-CoV-2 vaccines, the rapid transmission, the severity of infection, the absence of the protection on immunocompromised patients, the propagation of variants, the onset of infection and/or disease in vaccinated subjects and the lack of availability of worldwide vaccination require additional antiviral treatments. Since 1987, lactoferrin (Lf) is well-known to possess an antiviral activity related to its physico-chemical properties and to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 167 publications
0
14
0
Order By: Relevance
“…Coronavirus disease 2019 (COVID-19) is an acute respiratory infectious disease caused by SARS-CoV-2 virus infection, a highly pathogenic single-stranded (positive) RNA virus belonging to the β-coronavirus family responsible for the COVID-19 pandemic [ 91 , 92 , 93 ]. It mainly infects a person’s respiratory tract, causing fever, fatigue, headache and muscle aches, dry cough, and shortness of breath.…”
Section: The Role Of Lactoferrin In Lung Diseasesmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) is an acute respiratory infectious disease caused by SARS-CoV-2 virus infection, a highly pathogenic single-stranded (positive) RNA virus belonging to the β-coronavirus family responsible for the COVID-19 pandemic [ 91 , 92 , 93 ]. It mainly infects a person’s respiratory tract, causing fever, fatigue, headache and muscle aches, dry cough, and shortness of breath.…”
Section: The Role Of Lactoferrin In Lung Diseasesmentioning
confidence: 99%
“…So, Lf protects the gastrointestinal tract by exerting antiinflammatory activity through maintaining a balance between good and bad gut microbes and reducing the intestinal damage caused by the SARS-CoV-2 virus. 63 In a meta-analysis it was revealed that Lf reduces the risk of respiratory tract infections, so it can be used as an adjunct for the prevention and management of COVID-19. 72 In vitro studies reported that due to the availability, safety, and in vitro efficacy, Lf has protective effects against SARS-CoV-2 by modulating the antiviral immune response with a modest effect on infection.…”
Section: Reviewmentioning
confidence: 99%
“…So, Lf protects the gastrointestinal tract by exerting anti-inflammatory activity through maintaining a balance between good and bad gut microbes and reducing the intestinal damage caused by the SARS-CoV-2 virus. 63…”
Section: Health Benefits Of Lactoferrinmentioning
confidence: 99%
“…In addition, several authors have shown how bovine LF can interfere with SARS-CoV and SARS-CoV-2 infections in vitro by enhancing natural killer cell and neutrophil activities. In silico studies have further suggested a possible mechanism of action based on a direct binding of LF to SARS-CoV-2 S glycoprotein and inhibition of the virus access into host cells by competing for ACE binding 130,131.…”
mentioning
confidence: 99%